2019
DOI: 10.1007/s00220-019-03482-9
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Theta Functions, Strange Duality, and Odd Orthogonal Bundles on Curves

Abstract: This paper studies spaces of generalized theta functions for odd orthogonal bundles with nontrivial Stiefel-Whitney class and the associated space of twisted spin bundles. In particular, we prove a Verlinde type formula and a dimension equality that was conjectured by Oxbury-Wilson. Modifying Hitchin's argument, we also show that the bundle of generalized theta functions for twisted spin bundles over the moduli space of curves admits a flat projective connection. We furthermore address the issue of strange dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…In [40], Laszlo showed that the connection constructed by Hitchin and the one constructed by Tsuchiya-Ueno-Yamada [67] coincide under the natural identification between H 0 (M G (C), Det ⊗ℓ ) and V † 0 (C, g, ℓ). A similar result for twisted Spin groups was also proved by Mukhopadhyay-Wentworth [47]. The following questions are natural in the context of parabolic moduli spaces:…”
Section: Introductionsupporting
confidence: 55%
“…In [40], Laszlo showed that the connection constructed by Hitchin and the one constructed by Tsuchiya-Ueno-Yamada [67] coincide under the natural identification between H 0 (M G (C), Det ⊗ℓ ) and V † 0 (C, g, ℓ). A similar result for twisted Spin groups was also proved by Mukhopadhyay-Wentworth [47]. The following questions are natural in the context of parabolic moduli spaces:…”
Section: Introductionsupporting
confidence: 55%
“…An application of this fact is the following: Hitchin's construction [11] of a projectively flat connection on the space of generalized Spin(N ) theta functions works as well in the twisted case. This connection was used by the authors in [15] in their study of strange duality for odd orthogonal bundles.…”
Section: Resultsmentioning
confidence: 99%
“…The conjecture was proved in type A by Belkale [Bel08], and Marian-Oprea [MO07]. Abe in [Abe08] proved strange duality in the symplectic setting conjectured by Beauville [Bea06] (see also [Bel12]), and has been studied for other cases [Muk16a,Muk16b,BP10,MW19]. In [DGT19c, Question 1] it was asked whether there are analogous geometric interpretations of dual spaces for vector spaces of conformal blocks defined by vertex operator algebras.…”
Section: Particular Examples: Computing Degreesmentioning
confidence: 99%